2022
DOI: 10.1186/s12872-022-02640-7
|View full text |Cite
|
Sign up to set email alerts
|

Early initiation of tolvaptan is associated with early discharge in patients with heart failure regardless of age

Abstract: Background Elderly patients with heart failure (HF) have been observed to decrease activities of daily living (ADL) during hospitalization. Prevention of ADL decline from shortening of hospital stays is especially important in the elderly, because decreasing ADL is associated with poor prognosis. We investigated the relationship between the early initiation of tolvaptan (TLV) after hospitalization and the length of hospital stay in patients with HF aged younger than 80 years and aged 80 years a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 30 publications
1
9
1
Order By: Relevance
“…Previous studies have indicated that the early use of tolvaptan within 3 days of hospitalization was associated with a shortened length of hospital stay and improved in‐hospital outcomes 9,10 . On the contrary, our results indicate that early initiation of tolvaptan within 6 h of admission was not related to improved in‐hospital outcomes; moreover, the D2T time did not affect the length of hospital stay in our study ( Figure ).…”
Section: Discussioncontrasting
confidence: 82%
See 1 more Smart Citation
“…Previous studies have indicated that the early use of tolvaptan within 3 days of hospitalization was associated with a shortened length of hospital stay and improved in‐hospital outcomes 9,10 . On the contrary, our results indicate that early initiation of tolvaptan within 6 h of admission was not related to improved in‐hospital outcomes; moreover, the D2T time did not affect the length of hospital stay in our study ( Figure ).…”
Section: Discussioncontrasting
confidence: 82%
“…Over the past few years, several studies have been conducted to investigate the favourable effects of tolvaptan on clinical outcomes in HF patients under various situations 6,7 . Early initiation of tolvaptan, within a couple of days, provided immediate decongestion and better clinical outcomes, such as prevention of worsening renal function (WRF) and shortening of the length of hospital stay 8–10 …”
Section: Introductionmentioning
confidence: 99%
“…The EF was calculated using either the modified Simpson method (apical two‐ or four‐chamber view) or the Teichholz method (parasternal long‐axis view) 15 . Furthermore, the proportion of patients with HFpEF was also evaluated 16 . HFpEF was defined as EF > 50% according to the guidelines from the Japan Circulation Society, the American Heart Association, and the European Society of Cardiology 17–19 …”
Section: Methodsmentioning
confidence: 99%
“…15 Furthermore, the proportion of patients with HFpEF was also evaluated. 16 HFpEF was defined as EF > 50% according to the guidelines from the Japan Circulation Society, the American Heart Association, and the European Society of Cardiology. [17][18][19] VaSera VS-1500E (Fukuda Denshi Company, Ltd.) was used to measure the ABI and CAVI after 12 h of fasting in the morning following ADHF improvement.…”
Section: Physiological Functional Examinationsmentioning
confidence: 99%
“…We calculated the EF using either the modi ed Simpson method (apical two-or four-chamber view) or the Teichholz method (parasternal long-axis view) [16]. The proportion of patients with HFpEF was also evaluated [17]. HFpEF was de ned as EF > 50% according to some guidelines from the Japan Circulation Society, the American Heart Association, and the European Society of Cardiology [18,19,20].…”
Section: Physiological Functional Examinationsmentioning
confidence: 99%